Development of the framework for the controllers of the process base management system to meet the requirements for integration with other subsystems and to implement service functions and diagnostics service - Pupena, Alexander; Mirkevich, Roman; Klymenko, Oleh; Polupan, Volodymyr (Енергетика і автоматика, 2017)
We consider approaches to develop a framework for application of software for programmable logic controllers as components of the base system process control (BPCS) with regard to their integration with other systems (SCADA, SIS, BPCS, MES / MOM) and increased requirements to the diagnostic process and service process and equipment. The concept of software framework is designed for controllers of PAC (Process automation controller), based on open standards IEC 61131 and is not used for producing specific solutions. The structure and the internal implementation of library elements of the frame is based on ISA-88, ISA-95, ISA-106 (Draft) ideas which provide the simplest integration of control systems into a single integrated automated control system. The paper proposes mechanisms to improve the diagnosis of the process and the system, quickly setting up the system and restore its functionality after failures. The frame is a set of interrelated elements of library functions and function blocks, which are described at their interface level, interaction principles and algorithms of functioning. It is assumed that IEC 61131-3 languages will be used for the implementation of framework for the particular controller, but it is not a prerequisite. Set of frame elements can be expanded and supplemented with additional functionality without infringing the general principles. First time proposed universal structure for process control of milk production by using modern standards for construction of integrated automated control systems.